Bagaimana Akuntabilitas dan Transparansi Pengelolaan Anggaran Pendapatan dan Belanja Desa pada Desa Lubuk Tajau Kabupaten Sekadau? - Nur Fitriana Hamsyi; Slindri Sridewi; Rafles Ginting; Nina Febriana Dosinta (Jurnal Eksplorasi Akuntansi, 2023)
This study aimed to determine the accountability and transparency of the village government in managing the village revenue and expenditure budget (a case study in Lubuk Tajau Village, Sekadau District). This study used qualitative research with a case study approach. Data collection involved observation techniques, in-depth interviews, and documentation. The results of this study indicate that the accountability and transparency of the village government in managing the village revenue and expenditure budget in Lubuk Tajau Village, Sekadau Regency has been carried out in accordance with Permendagri No. 20 of 2018, but there are still obstacles such as delays in submitting accountability reports to the government caused by rules that sometimes change.